2020
DOI: 10.1155/2020/1461459
|View full text |Cite
|
Sign up to set email alerts
|

Image Retrieval Based on a Multi-Integration Features Model

Abstract: Feature integration theory can be regarded as a perception theory, but the extraction of visual features using such a theory within the CBIR framework is a challenging problem. To address this problem, we extract the color and edge features based on a multi-integration features model and use these for image retrieval. A novel and highly simple but efficient visual feature descriptor, namely, a multi-integration features histogram, is proposed for image representation and content-based image retrieval. First, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 41 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…To assess the performance and effectiveness of the image retrieval process, the value of precision and recall is calculated as follows [10], [30]:…”
Section: Performance Evaluationmentioning
confidence: 99%
“…To assess the performance and effectiveness of the image retrieval process, the value of precision and recall is calculated as follows [10], [30]:…”
Section: Performance Evaluationmentioning
confidence: 99%
“…4) EDBTC [58] and MIFM [59] methods, which depend on extracting both texture and color features. Our proposed method gave better performance than previous methods regarding Precision, Recall, mAP, and ARR for all databases, because it works on extracting the color changes of minimum and maximum intensities of images blocks, in addition to the texture features of the images.…”
Section: A First Experiment: Image Retrieval Using Fdlnpmentioning
confidence: 99%
“…Feature addition stands out for its high accuracy [24]. Chu et al [25] proposed a multi-modal feature fusion method based on weight distribution, and demonstrated that the method significantly outperforms single feature fusion. In addition to the extracted features like tongue color, moss thickness, and face color, PSQI score (rang: 0-21) and sleep structure score (range: 0-100) were adopted to indicate sleep quality.…”
Section: Hemies Design and Implementationmentioning
confidence: 99%